2021
DOI: 10.1177/2042018821995370
|View full text |Cite
|
Sign up to set email alerts
|

Normocalcaemic primary hyperparathyroidism: what is the role of parathyroid surgery?

Abstract: Primary hyperparathyroidism (PHPT) is classically associated with both an elevated or ‘inappropriately normal’ parathyroid hormone (PTH) level and raised serum calcium. However, in clinical practice, increasing numbers of patients present with raised PTH but normal serum calcium, renal function and vitamin D; this is known as normocalcaemic PHPT (nPHPT). Studies investigating the clinical presentation of this condition have shown that patients may present with hypertension, nephrolithiasis, impaired glucose to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…We could not determine the postoperative correlation between PTH and FGF23 because postoperative plasma PTH values were not measured. Current review showed that measuring of postoperative plasma PTH values could be supplied by the continuously monitored albumin-adjusted serum calcium followed with clinical investigations including symptoms of hypercalcemia and presence of end organ diseases (renal stones, fragility fractures and osteoporosis) ( 25 ). We could not evaluate the continuously monitored calcium/albumin levels due to the fact that we assayed plasma samples and postoperative serum calcium levels were retrieved from medical notes.…”
Section: Discussionmentioning
confidence: 99%
“…We could not determine the postoperative correlation between PTH and FGF23 because postoperative plasma PTH values were not measured. Current review showed that measuring of postoperative plasma PTH values could be supplied by the continuously monitored albumin-adjusted serum calcium followed with clinical investigations including symptoms of hypercalcemia and presence of end organ diseases (renal stones, fragility fractures and osteoporosis) ( 25 ). We could not evaluate the continuously monitored calcium/albumin levels due to the fact that we assayed plasma samples and postoperative serum calcium levels were retrieved from medical notes.…”
Section: Discussionmentioning
confidence: 99%
“…Presumably, reduction in serum PTH levels associated with rs12654812 may result from a decrease in serum phosphate levels caused by diminished renal reabsorption. Since patients with hyperparathyroidism are usually associated with impair glucose tolerance ( Aojula et al, 2021 ), that kidney stone variance may negatively correlated with serum glucose level through decreased serum PTH.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, neither the guidelines of the Fourth International Workshop 80 or the American Society of Endocrine Surgeons 5 mention that parathyroidectomy in patients with NCHPT improves BMD, cardiovascular risk factors, and quality of life, which has been shown by several recent studies. 57,[101][102][103][104] Parathyroid imaging studies are appropriate once it has been established that a patient has NcPHPT and surgery is considered. Unfortunately, there is limited data on the utility of imaging in patients with NcPHPT and the data available are conflicting.…”
Section: Normocalcemic Phptmentioning
confidence: 99%